Are we providing modern anesthetics services in the Kingdom of Saudi Arabia? - Seraj, Mohamed Abdullah (Medknow Publications & Media Pvt Ltd, 2012)
This illustrated detailed article will describe history of over forty years struggle, of hardship and discrimination to the specialty. I have with my colleagues faced obstacles and disappointments during the development of modern anaesthesia services with its subspecialties in Saudi Arabia. I have all support and encouragement from the top authorities of the university. I have managed to establish a top class anaesthesia department, Saudi Anaesthetic Association and the King Saud Fellowship in anaesthesia and intensive care within one decade. The next decade was assigned for expansion to create the Arab Board of anaesthesia and Intensive Care followed by the Saudi Specialty of anaesthesia and intensive care and its fellowship in different Subspecialties. I always wonder within myself, have I and my colleagues achieved our goal and did we do well.